Dielectric properties of coal in the terahertz frequency region of 100–500 GHz. (15th January 2017) - Fan, Wei; Chang, Tianying; Liu, Lingyu; Cui, Hong-Liang
Abstract: The dielectric properties of anthracite and bituminous coals were investigated in the terahertz (THz) frequency region from 100 GHz to 500 GHz. We developed two types of THz material measurement systems that can be operated in this frequency region, including one based on a vector network analyzer (VNA) with frequency extension modules, and another based on a THz time-domain spectroscopy (TDS) system. Employing the free-space configuration, we obtained the variation of dielectric property of coals in the frequency region of 100–500 GHz. By comparing the VNA and TDS systems, we evaluated the continuity and consistency of the two systems and verified the dielectric property measurement results of coal in the entire frequency region. We first outlined the fundamental theory of dielectric property with both methods, followed by estimating the measurement error in consideration with the system stability, the time span of the time-domain gating, and measurement uncertainty. We evaluated the dielectric property of coal samples through the measured results of the VNA and TDS systems. Comparison is also made of the variation of measured dielectric property with the lower THz frequency region (W-band) in our previous work. The results show that different coal type exhibited different variation with increasing frequency in the THz band considered.